2018
DOI: 10.1021/acs.analchem.8b00142
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Hybrid Three-Dimensional Gas Chromatography with Accurate Mass Spectrometry: A Novel Tool for High-Resolution Characterization of Multicomponent Samples

Abstract: A novel sequential three-dimensional gas chromatography-high-resolution time-of-flight mass spectrometry (3D GC-accTOFMS) approach for profiling secondary metabolites in complex plant extracts is described. This integrated system incorporates a nonpolar first-dimension (D) separation step, prior to a microfluidic heart-cut (H/C) of a targeted region(s) to a cryogenic trapping device, directly followed by the rapid reinjection of a trapped solute into a polar second-dimension (D) column for multidimensional sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…The alkaline mixture standard (C9–C40) were analyzed by the same program in GC-MS. The identification of components were assigned by the software GC-MS Postrun analysis (Shimadzu, Kyoto, Japan) by searching MS data and retention indices in National Institute of Standards and Technology (NIST, Washington DC, USA) and referring to previous reports [30,31]. Areas were recorded for all detectable peaks.…”
Section: Methodsmentioning
confidence: 99%
“…The alkaline mixture standard (C9–C40) were analyzed by the same program in GC-MS. The identification of components were assigned by the software GC-MS Postrun analysis (Shimadzu, Kyoto, Japan) by searching MS data and retention indices in National Institute of Standards and Technology (NIST, Washington DC, USA) and referring to previous reports [30,31]. Areas were recorded for all detectable peaks.…”
Section: Methodsmentioning
confidence: 99%
“…Banana Terra spirits were investigated for the first time by the authors, who identified 18 aroma-impact regions, and the main odorants found were 3-methylbutan-1-ol, 3-methylbutan-1-ol acetate, 2-phenylethylacetate and phenylethyl alcohol [89]. The same group also studied hop essential oil [12,52,83,84], identifying some of its impact odorants, such floral notes such as geraniol, linalool, β -ionone, and eugenol, and a compound responsible for woody/spicy aroma, 4-hydroxy- β -caryophyllene.…”
Section: Drinks and Beveragesmentioning
confidence: 99%
“…Marriott and co-workers [12,109] assessed the composition of Agarwood ( Aquilaria malaccensis ) oils through different multidimensional approaches. An integrated 3D GC-GC×GC system was used to improve the resolution of oxygenated sesquiterpenes of Agarwood (Figure 7).…”
Section: Woodmentioning
confidence: 99%
See 2 more Smart Citations